2015
DOI: 10.1007/s00428-015-1854-0
|View full text |Cite
|
Sign up to set email alerts
|

Secretory IgA from submucosal glands does not compensate for its airway surface deficiency in chronic obstructive pulmonary disease

Abstract: Secretory immunoglobulin A (SIgA) reaches the airway lumen by local transcytosis across airway epithelial cells or with tracheobronchial submucosal gland secretions. In chronic obstructive pulmonary disease (COPD), deficiency of SIgA on the airway surface has been reported, however, reduction of SIgA levels in sputum and bronchoalveolar lavage (BAL) has not been consistently observed. To explain this discrepancy, we analyzed BAL fluid and lung tissue from patients with COPD and control subjects. Immunohistoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
20
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 36 publications
3
20
1
Order By: Relevance
“…In 2001, Pilette and coworkers (13) reported that secretory component expression is reduced in airways of patients with COPD. Subsequently, we showed that pIgR expression is down-regulated in COPD and that airway surface SIgA deficiency is widespread in COPD and correlates with severity of airflow obstruction (14,15). Consistent with these observations, cultured airway epithelial cells from patients with COPD were reported to express lower levels of pIgR than airway epithelial cells from healthy control subjects (16).…”
mentioning
confidence: 52%
“…In 2001, Pilette and coworkers (13) reported that secretory component expression is reduced in airways of patients with COPD. Subsequently, we showed that pIgR expression is down-regulated in COPD and that airway surface SIgA deficiency is widespread in COPD and correlates with severity of airflow obstruction (14,15). Consistent with these observations, cultured airway epithelial cells from patients with COPD were reported to express lower levels of pIgR than airway epithelial cells from healthy control subjects (16).…”
mentioning
confidence: 52%
“…1,3 Roy and colleagues showed that Muc5b, but not Muc5ac, was required for airway defense and that the decrease of Muc5b could hamper mucus clearance. 19 Additionally, publications have stated that the levels of MUC5B in BALF and sputum were increased in COPD patients, [32][33][34] while carbocisteine could balance fucosylated and sialylated sugar chains, 13 normalize the viscous property of mucus 12 and reduce MUC5AC expression. We speculated that the decrease of Muc5b might have played an important role in COPD pathogenesis and carbocisteine might reduce the expression of Muc5b in COPD mice model.…”
Section: Discussionmentioning
confidence: 99%
“…In 2001, Pilette et al reported that SC expression was reduced in airways of COPD (11). Subsequently, researchers found that patients with COPD had reduced SIgA in bronchoalveolar lavage (12). Polosukhin et al have shown that pIgR expression is down-regulated in COPD and that SIgA deficiency is correlated with severity of airflow obstruction(13).…”
Section: Introductionmentioning
confidence: 99%